The Influence of Work Environment and Work Discipline on Employee Performance at Waled Regional Hospital, Cirebon Regency - Aura Choirunisa; Lisa Harry Sulistiyowati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the influence of the work environment and work discipline on the performance of health workers (nakes) at Waled Regional General Hospital, Cirebon Regency. This study uses a quantitative approach with a survey method. The study population was all health workers at Waled Regional General Hospital, Cirebon Regency with a sample of 175 respondents determined using the Slovin technique. Data were collected through a Likert scale questionnaire and analyzed using IBM SPSS Statistics. Data analysis techniques include validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analyses, coefficients of determination, and hypothesis tests (t-test and F-test). The results showed that the work environment had a positive and significant effect on employee performance with a regression coefficient of 0.398, a calculated t-value of 7.293, and a significance of 0.000 <0.05. Work discipline also had a positive and significant effect on employee performance with a regression coefficient of 0.605, a calculated t-value of 10.797, and a significance of 0.000 <0.05. The results of the simultaneous test indicate that the work environment and work discipline significantly influence employee performance. The coefficient of determination indicates that variations in employee performance can be explained by the work environment and work discipline, while the remaining variation is influenced by other factors outside the study. Work discipline is the most dominant variable influencing employee performance. This research is expected to provide consideration for hospital management in improving employee performance.